A Bibliometric and Visual Analysis of Nanocomposite Hydrogels Based on VOSviewer From 2010 to 2022 - Zhao, Mingyi; Zhang, Hanqi; Li, Zixin (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Nanocomposite hydrogels (NHs) is a stable composite material formed by dispersing nanomaterials in the hydrogel, which has a broad development prospect in the biomedical field. In this study, we aimed to evaluate biomedical applications of NHs about trends and hotspots systematically and comprehensively from 2010 to 2022. Methods: The 714 articles and reviews related to NHs applications in the biomedical field from 2010 to 2022 were retrieved from the Web of Science Core Collection (WOSCC). Two scientometric software (VOSviewer and Microsoft Excel 2019) were used to visually bibliometric analysis in terms of research trends, sources, the contribution of Journals, co-citation, and the co-occurrence of keywords. Results: From 1 January 2010 to 3 February 2022, the number of annual scientific publications about NHs exhibits an upward trend, and research articles were published in a larger proportion (more than 77%). The top 3 countries in the NHs research were China, the United States, and India; meanwhile, Tabriz University of Medical Sciences, Chinese Academy of Sciences, and the Tshwane University of Technology were most active and contributive. In the contribution of journals, the journal Advanced Functional Materials had the highest number of publications, and the journal Int J Biol Macro had the most citation. Varaprasad K was the most prolific author and Haraguchi K ranked first among co-cited authors. In the ranking of frequency in the co-cited references, nanocomposite Hydrogels for Biomedical Applications published by Gaharwar AK is the most frequently cited reference. The keyword with the highest frequency is “drug delivery”. Conclusion: This study performed a full overview of NHs using bibliometric, concluded current trends and hot spots. The information may help researchers focusing on NHs identified the development in this field.